Patients’ perspectives on delayed diagnosis of inflammatory bowel disease : a qualitative analysis : a thesis presented in partial fulfillment of requirements for the degree of Master of Arts in Psychology at Massey University, Auckland, New Zealand - Dyson, Hannah (Massey University, 2024)
Aotearoa has increasingly high levels of inflammatory bowel disease (IBD) but low rates of timely diagnosis. Despite this, the impacts of a diagnostic delay (DD) for a patient with IBD are poorly understood. It is necessary to investigate the IBD patient’s perspectives on the barriers and impacts of their DD. Previous quantitative research has been conducted to assess the implications of a DD, but qualitative research investigating patient’s perceptions is in its infancy. This study aimed to identify what diagnosed IBD patients consider the main barriers to diagnosis and the relevant impacts of DD. Understanding how a DD can contribute to various negative psychosocial impacts is essential. Ten participants with diagnosed IBD who felt they experienced a DD were interviewed to discuss their experience. Interviews were transcribed verbatim and analysed using Braun and Clarke’s (2006) reflexive thematic analysis. Four themes were identified. A lack of IBD awareness and quality of care were considered significant contributors to delay. Psychosocial impacts of ‘Alive, but not living’ and ‘Why so stressed?’ were identified as participants’ perceived emotional impacts of delay, including connecting feelings of helplessness, frustration and resentment towards the health system. The findings produce an incentive to raise IBD awareness and diagnostic procedures to reduce delay time, with recommendations to introduce a holistic model of care for individuals with IBD symptoms. Further research is required to understand how subjective, retrospective recall can influence participant responses, and understanding general practitioners’ perspectives of delay is warranted.
Keywords: 520304 Health psychology